A hybrid multi-criteria decision making technique to improve the quality of hotel industry services in Mashhad City. (2017) - Mohaghar, Ali; Eghbal, Roya; Bazazzadeh, Seyed Hojjat
Service industry is one of the most lucrative industries in the 21st century. To survive and succeed in competitive markets, service organisations pay special attention to the quality of their services. In between, hotel industry, as one of the most important parts of booming tourism industry in each country, has always been considered. The goal of conducting this study is to identify and rank the factors affecting the improvement of the quality of hotel industry services. For this purpose, 21 components were identified reviewing research literature and experts' views; and finally, two FUZZY ANP and FUZZY TOPSIS methods prioritised using combination method. The conclusion showed that having new and up-to-date hotel equipments, having professional staff for hoteling services and respecting customers are the first priorities. Therefore, regarding the above factors, it is suggested to hotel managers, to work on advancing services quality presented by this industry.